Penggunaan Parameter Geokimia Isoprenoid untuk Menentukan Tingkat Kematangan Minyak Bumi (Crude Oil) Sumur Minyak Langgak Riau - Emrizal Mahidin Tamboesai (Jurnal Kimia Valensi, 2015)
In this study, crude oil samples from Distric Langgak, Riau were tested and characterized with isoprenoid parameters. Determination of thermal maturity level aims to determine the feasibility of petroleum wells to be exploited because there are many new wells of petroleum unexploited in the Riau area. Determination of maturity crude oil performed by analysis saturated fractions. Saturated fraction of the wells Langgak used to determine the maturity of crude oil based on parameters isoprenoid, n-alkane and carbon preference index were analyzed using gas chromatography-flame ionize detector (GC-FID). Based on the value Pr / Ph, Pr / n-C17, Ph / n-C18 and its CPI, the maturity level of petroleum from oil wells, Langgak levels of maturity and quality of the oil is indicated by the value of Pr / Ph (2.27), the value of Pr / n-C17 (0.57), the value of Ph / n-C18 (0.22) and the CPI (1.087) respectively.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3142